ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INVESTASI ASING LANGSUNG DI EMPAT NEGARA ASEAN - Putri, Anissa Triana; Karmini, Ni Luh (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.11.TAHUN.2024DO - 10.24843/EEB.2024.v13.i11.p13, 2024)
Foreign direct investment is one of the alternative sources of financing that comes from abroad to help the economic development of a country. Many countries open up and open the widest investment tap to be able to increase development and spur the country's economic growth. This research aims to find out the factors that affect foreign direct investment. This research analyzed the effect of economic growth, interest rates, and trade openness on foreign direct investment in four ASEAN countries (Singapore, Indonesia, Vietnam, and Malaysia) from 2006-2020. This research uses panel data analysis with a fixed effect model. The results show that simultaneously, economic growth, interest rates, and trade openness affect foreign direct investment in four ASEAN countries. Partially, economic growth have a positive and significant effect on foreign direct investment in four ASEAN countries, while interest rates and trade openness have a negative and insignificant effect on foreign direct investment in four ASEAN countries. The implication of this study is that rising economic growth will increase foreign direct investment, and high interest rates and trade openness will decrease investment even though it is not significant.